2017
DOI: 10.1007/s00464-017-5532-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of self-pulling and latter transected delta-shaped Billroth-I anastomosis in totally laparoscopic distal gastrectomy

Abstract: Background We developed a modified delta-shaped gastroduodenostomy technique in totally laparoscopic distal gastrectomy. This novel technique, which effectively reduces the required quantity of linear stapler [1][2][3], was named as self-pulling and latter transected delta-shaped anastomosis (Delta SPLT) [4]. Methods Delta SPLT was performed on 15 patients with stage cT1-2 antral cancer. We ligated the duodenum with a rope instead of transecting it and used the ligature rope to pull the duodenum during the who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This study examined the e cacy and safety of SPLT-TLTG surgery compared to conventional LATG surgery. Consistent with other studies [4][5]9] , our study suggested that SPLT-TLTG surgery has the advantages of minimally invasive, reduced bleeding and rapid postoperative recovery. Meanwhile, avoid squeezing tumor tissue during the operation, which diminishes the risk of rupture and dissemination of the tumor during the operation [9] .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study examined the e cacy and safety of SPLT-TLTG surgery compared to conventional LATG surgery. Consistent with other studies [4][5]9] , our study suggested that SPLT-TLTG surgery has the advantages of minimally invasive, reduced bleeding and rapid postoperative recovery. Meanwhile, avoid squeezing tumor tissue during the operation, which diminishes the risk of rupture and dissemination of the tumor during the operation [9] .…”
Section: Discussionsupporting
confidence: 91%
“…However, the technique di culties, especially during anastomose, impedes the wide use of this advanced surgery. A Chinese surgical team introduced a new anastomosis method, selfpulling and latter transection (SPLT) esophagojejunostomy after traction based on the overlap and functional end-to-end anastomosis (FETE) in TLTG [4] [5] . Their study indicated that SPLT is a simple and secure process that helped to apply TLTG surgery on patients with more advanced stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the technical difficulty and quantity of anastomotic instruments used, a modified DA technique named the "self-pulling and latter transected delta-shaped gastroduodenostomy" (Delta SPLT) was developed in 2016. 6 It requires only one stapler and four 60-mm cartridges, and it does not require any suturing by hand. This study was conducted to evaluate the postoperative safety and feasibility of the Delta SPLT technique by analyzing the surgical outcomes in the first year after the surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In general, DA requires high‐level coordination between the operator and assistant, at least one endoscopic linear stapler, and five cartridges. To reduce the technical difficulty and quantity of anastomotic instruments used, a modified DA technique named the “self‐pulling and latter transected delta‐shaped gastroduodenostomy” (Delta SPLT) was developed in 2016 6 . It requires only one stapler and four 60‐mm cartridges, and it does not require any suturing by hand.…”
Section: Introductionmentioning
confidence: 99%